2017
DOI: 10.1136/archdischild-2016-312360
|View full text |Cite
|
Sign up to set email alerts
|

T-piece versus self-inflating bag ventilation in preterm neonates at birth

Abstract: This study is the first that highlights the effectiveness of T-piece resuscitator ventilation in improving relevant outcomes in preterm neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 22 publications
(17 reference statements)
1
29
0
2
Order By: Relevance
“…They demonstrated that neonates in TPR group required positive pressure ventilation for a lesser duration and had lower intubation rates [16]. A Brazilian prospective cohort study of 1962 inborn preterm infants showed that TPR, as compared to SIB, increased the odds of survival to discharge without major morbidities [17]. In the present study, the requirement of second dose of surfactant was significantly lower in the TPR group.…”
Section: Discussionsupporting
confidence: 47%
“…They demonstrated that neonates in TPR group required positive pressure ventilation for a lesser duration and had lower intubation rates [16]. A Brazilian prospective cohort study of 1962 inborn preterm infants showed that TPR, as compared to SIB, increased the odds of survival to discharge without major morbidities [17]. In the present study, the requirement of second dose of surfactant was significantly lower in the TPR group.…”
Section: Discussionsupporting
confidence: 47%
“…After adjusting for important maternal and infant demographic characteristics, infants who received PPV with the T-piece were significantly more likely to survive to discharge without bronchopulmonary dysplasia or severe intraventricular hemorrhage, or periventricular leukomalacia. [64]…”
Section: Clinical Evidence For the Most Effective Methods To Provide mentioning
confidence: 99%
“…Outcome measures included survival to hospital discharge without bronchopulmonary dysplasia, severe peri-intraventricular haemorrhage, and periventricular leukomalacia. The study showed that the T-piece resuscitator resulted in patients being more likely to survive to hospital discharge while avoiding major morbidities 30 .…”
Section: Neonatal Mask Ventilationmentioning
confidence: 97%